Gut microbiota and its metabolites regulate insulin resistance: traditional Chinese medicine insights for T2DM - Liu, Jing; Li, Fuxing; Yang, Le; Luo, Shengping; Deng, Yihui (Frontiers in Microbiology, 2025)
The gut microbiota is closely associated with the onset and development of type 2 diabetes mellitus (T2DM), characterized by insulin resistance (IR) and chronic low-grade inflammation. However, despite the widespread use of first-line antidiabetic drugs, IR in diabetes and its complications continue to rise. The gut microbiota and its metabolic products may promote the development of T2DM by exacerbating IR. Therefore, regulating the gut microbiota has become a promising therapeutic strategy, with particular attention given to probiotics, prebiotics, synbiotics, and fecal microbiota transplantation. This review first examines the relationship between gut microbiota and IR in T2DM, summarizing the research progress of microbiota-based therapies in modulating IR. We then delve into how gut microbiota-related metabolic products contribute to IR. Finally, we summarize the research findings on the role of traditional Chinese medicine in regulating the gut microbiota and its metabolic products to improve IR. In conclusion, the gut microbiota and its metabolic products play a crucial role in the pathophysiological process of T2DM by modulating IR, offering new insights into potential therapeutic strategies for T2DM.